The negative campaign as an electoral strategy from the perspective of political consultants: who to attack, when to attack and how to attack (Intercom - Brazilian Journal of Communication Sciences, 2022)
This article analyzes negative advertising as an electoral strategy. The objective is to assess three basic questions: who to attack, when to attack and how to attack. To do so, we conducted a research survey with a sample of Brazilian political consultants in order to understand how negative campaign strategies vary according to the circumstances. The results indicate that the decision to attack the opponent should be used in the final stage of the campaign, focusing on the opponent’s proposals and preferably via social networks. The decision about who to attack is influenced by the expectation of victory and positioning in the polls, but the dynamics of voting intentions change the target of the attacks and the intensity with which negative advertising should be used.
Keywords: Elections; Public Opinion; Negative Campaign; Electoral Campaign; Expert Survey